STILISTIKA HADIS: ANALISIS AL-MUSTAWAYAT AL-USLUBIYAH PADA HADIS-HADIS ARBA’IN NAWAWI - Mohammad Dzulkifli; Lukman Fajariyah (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
This study aims to analyze the language style of Arbain Nawawi's hadith using modern linguistic theory, namely stylistics. Hadith as the second source of Islamic law after the Qur'an has a distinctive language style that is interesting to study from a linguistic perspective to obtain a more objective and comprehensive meaning. This research is descriptive qualitative research using the literature study method. The data used are qawli hadiths in the book Arba'in al-Nawawi written by Imam an-Nawawi. The data collection technique used a note-taking technique and data analysis was carried out using the stylistic analysis technique from the perspective of Syihabuddin Qalyubi which consists of five levels of analysis; phonological, morphological, syntactic, semantic, and imagery levels. The results of this study indicate that the hadiths of Arba'in al-Nawawi have a variety of consonant sounds, namely; plosives, fricatives, nasals, laterals, and trills. From the aspect of morphology and syntax, there is a special choice of words that are not used in the Qur'an, both in terms of words, sentences, and expressions. Arba'in Nawawi's hadith language also contains semantic elements such as polysemy, antonyms, synonyms, and lexical meanings. As for the imagery aspect, the researcher found uslub tasyb?h, majaz, and kin?yah which are found in almost all of the forty hadiths.